Socially shared regulation of learning and participation in social interaction in collaborative learning - Isohätälä, Jaana; Järvenoja, Hanna; Järvelä, Sanna (International journal of educational research, 2017)
•SSRL involved more active participation than task-focused interaction overall.•SSRL often emerged when participation increased to a higher level than general.•SSRL as a strategic activity had a role in the dynamics of participation. This study investigated how socially shared regulation of learning (SSRL) emerged during the fluctuation of participation in interaction in collaborative learning. Twenty-four student teachers in six small groups were video-recorded during collaborative tasks in mathematics. Manifestations of SSRL and students’ participation were micro-analytically coded. Next, the concurrence between manifestations of SSRL and the fluctuation of participation was examined and illustrative examples were described. The results show that SSRL involved more active participation than task-focused interaction overall and that SSRL often coincided with increases in participation to a higher level than general. The findings suggest that manifestations of SSRL involved activated participation during the moments when interaction was needed to reciprocally resolve situative challenges and to coordinate activities.